2014
DOI: 10.3389/fphys.2014.00134
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of soluble guanylate cyclase by matricellular thrombospondins: implications for blood flow

Abstract: Nitric oxide (NO) maintains cardiovascular health by activating soluble guanylate cyclase (sGC) to increase cellular cGMP levels. Cardiovascular disease is characterized by decreased NO-sGC-cGMP signaling. Pharmacological activators and stimulators of sGC are being actively pursued as therapies for acute heart failure and pulmonary hypertension. Here we review molecular mechanisms that modulate sGC activity while emphasizing a novel biochemical pathway in which binding of the matricellular protein thrombospond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 201 publications
(294 reference statements)
1
30
0
Order By: Relevance
“…27 It was previously reported that an uncommon urticaria-like neutrophilic dermatosis serves as a sign of the presence of IgA myeloma. 37 What worth mentioning is that from the screen of relative gene and prediction of miRNA, we found that miR-194 could regulate THBS1, thereby regulating the TGF-β and influencing the development of CIU. IgG is a main choice of cancer treatment, particularly in patients with metastatic or advanced cancers.…”
Section: Discussionmentioning
confidence: 91%
“…27 It was previously reported that an uncommon urticaria-like neutrophilic dermatosis serves as a sign of the presence of IgA myeloma. 37 What worth mentioning is that from the screen of relative gene and prediction of miRNA, we found that miR-194 could regulate THBS1, thereby regulating the TGF-β and influencing the development of CIU. IgG is a main choice of cancer treatment, particularly in patients with metastatic or advanced cancers.…”
Section: Discussionmentioning
confidence: 91%
“…The reduction in cGMP levels we observed in partially CD36 deficient AA women is opposite to what would be predicted based on the in vitro inhibition of the NO-sGC pathway by TSP1-CD36 engagement. However, TSP1 can potently inhibit vascular NO signaling via its other receptor CD47, and CD36 deletion might enhance TSP1 availability for binding CD47 (22,23,34). Possibly CD36 binding TSP1 buffers the more potent inhibitory effect on TSP1 signaling via CD47.…”
Section: Discussionmentioning
confidence: 95%
“…This receptor is abundant in vascular endothelial cells, especially in heart, skeletal muscle and adipose tissue (17) where it facilitates highaffinity tissue FA uptake (18,19) and cellular FA metabolism (20). TSP1 binding to CD36 (21,22) or its other receptor CD47 (23) suppresses NO-cGMP signaling in cultured endothelial cells but whether CD36 contributes to NO-mediated vascular effects in vivo remains unknown. In the present study, we tested the hypothesis that the G allele of CD36 coding SNP rs3211938 (G/T), which is 10-times more common in AA (genotype frequency of ϳ20%) as compared to Caucasians and results in ϳ50% reduced CD36 expression (24) would associate with altered endothelial function (Protocol 1).…”
mentioning
confidence: 99%
“…TSP-1 also inhibits non-NO activation of sGC [23]. TSP-1 has been implicated as a contributor to platelet hyperaggregability [13], although the potential importance of this relationship has not been previously reported in patients with AF.…”
Section: Discussionmentioning
confidence: 99%